Shorting Factor In‐Flight Calibration for the Van Allen Probes DC Electric Field Measurements in the Earth's Plasmasphere. Issue 4 (30th April 2019) - Lejosne, Solène; Mozer, F. S.
Abstract: Satellite‐based direct electric field measurements deliver crucial information for space science studies. Yet they require meticulous design and calibration. In‐flight calibration of double‐probe instruments is usually presented in the most common case of tenuous plasmas, where the presence of an electrostatic structure surrounding the charged spacecraft alters the geophysical electric field measurements. To account for this effect and the uncertainty in the boom length, the measured electric field is multiplied by a parameter called the shorting factor (sf ). In the plasmasphere, the Debye length is very small in comparison with spacecraft dimension, and there is no shorting of the electric field measurements (sf = 1). However, the electric field induced by spacecraft motion greatly exceeds any geophysical electric field of interest in the plasmasphere. Thus, the highest level of accuracy in calibration is required. The objective of this work is to discuss the accuracy of the setting sf = 1 and therefore to examine the accuracy of Van Allen Probes electric field measurements below L = 2. We introduce a method to determine the shorting factor near perigee. It relies on the idea that the value of the geophysical electric field measured in the Earth's rotating frame of reference is independent of whether the spacecraft is approaching perigee or past perigee, that is, it is independent of spacecraft velocity. We obtain that sf = 0.994 ± 0.001. The resulting margins of errors in individual electric drift measurements are of the order of ±0.1% of spacecraft velocity (a few meters per second). Plain Language Summary: Large‐scale electric fields are naturally present in space. They are key to understanding plasma dynamics. Yet they are notoriously difficult to measure directly. In situ electric field measurements are especially challenging very close to Earth, when spacecraft pass through perigee with maximum velocity in a strong magnetic field. The field instruments onboard the Van Allen Probes are the first to be accurate enough to measure the geophysical electric field around magnetic equator, even below 3 Earth radii. In this work, we introduce a method to calibrate the data and to determine the margins of errors for the Van Allen Probes electric drift measurements in the Earth's plasmasphere. The corresponding margins of errors are remarkably small (<10 m/s for each individual electric drift measurement). Therefore, this work further demonstrates the ability of Van Allen Probes instruments to resolve small variations in the geophysical electric drift, even very close to Earth. It is the first time that the calibration of near perigee DC electric field measurements is discussed. Such method could potentially be transposed to other missions and other sets of satellite‐based electric field measurements to further advance our understanding of transport and energization in space plasmas. Key Points: Electric field experiments require calibration of the shorting factor, a parameter that converts measurements into actual electric field We present a method to determine the shorting factors of the Van Allen Probes double‐probe electric field instruments near perigee Uncertainty in individual electric drift measurements due to uncertainty in the value of the shorting factor is smaller than 10 m/s